ANALISIS PERUBAHAN VISUAL KARAKTER PADA GIM COOKIE RUN KINGDOM - Ika Resmika Andelina; Sherly Theresia (Jurnal Dimensi DKV Seni Rupa dan Desain, 2023)
Cookies Character Design Development Analysis in Cookie Run Kingdom When viewed statistically on the play store, City-building Simulation Role Playing Games such as Cookie Run Kingdom are a type of game that is quite popular among players. The visualization is interesting, especially in the character design which uses an anthropomorphic style from the basic shape of the GingerBread Man cookie, which is one of the aspects that sells even though it uses an unusual style like anime and cartoon styles in general games. However, this popular character design can actually experience significant changes from visualization to character stories (lore) when it gets the influence of mixing from other elements and still gets a good response from the players. These changes to the character design will be further dissected to explore the elements that are mixed and removed in the character to create a new design. The shape matrix of the manga matrix technique will be used to dissect the elements that become the mix of cookie character designs, so that the results of the research can be used as reference material for character designers to use the manga matrix approach, which is reinforced by anthropomorphism techniques in creating new characters or redesigning them. unique, using a style that is not common but still captivates players. Keywords: character design, antropohomorfism, game, manga matrix